2016
DOI: 10.1002/etc.3245
|View full text |Cite
|
Sign up to set email alerts
|

Assessing variability in chemical acute toxicity of unionid mussels: Influence of intra‐ and interlaboratory testing, life stage, and species

Abstract: The authors developed a toxicity database for unionid mussels to examine the extent of intra- and interlaboratory variability in acute toxicity tests with mussel larvae (glochidia) and juveniles; the extent of differential sensitivity of the 2 life stages; and the variation in sensitivity among commonly tested mussels (Lampsilis siliquoidea, Utterbackia imbecillis, and Villosa iris), commonly tested cladocerans (Daphnia magna and Ceriodaphnia dubia), and fish (Oncorhynchus mykiss, Pimephales promelas, and Lepo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(60 citation statements)
references
References 33 publications
8
47
5
Order By: Relevance
“…Previous studies have demonstrated that interlaboratory variation of toxicity tests performed on the same species and chemical may be as great as 5-fold [15,30], suggesting that tests with surrogate species conducted in different laboratories and/or different test conditions may not show as close agreement to fairy shrimp from the present study. Previous studies have demonstrated that interlaboratory variation of toxicity tests performed on the same species and chemical may be as great as 5-fold [15,30], suggesting that tests with surrogate species conducted in different laboratories and/or different test conditions may not show as close agreement to fairy shrimp from the present study.…”
Section: Ice Model Predictionsmentioning
confidence: 52%
“…Previous studies have demonstrated that interlaboratory variation of toxicity tests performed on the same species and chemical may be as great as 5-fold [15,30], suggesting that tests with surrogate species conducted in different laboratories and/or different test conditions may not show as close agreement to fairy shrimp from the present study. Previous studies have demonstrated that interlaboratory variation of toxicity tests performed on the same species and chemical may be as great as 5-fold [15,30], suggesting that tests with surrogate species conducted in different laboratories and/or different test conditions may not show as close agreement to fairy shrimp from the present study.…”
Section: Ice Model Predictionsmentioning
confidence: 52%
“…A MATC for length was used when an EC20 could not be estimated based on any endpoints in the 4-wk exposure of the 4-to 12-wk test in 2014 (Table 3), and a MATC for biomass was used when EC20s for growth and biomass had broad confidence limits in the 2015 test started with 1-mo-old mussels (Table 4). A factor of 2 difference was reported for several mussel species in repeated acute exposures (Wang et al 2007b;Raimondo et al 2016). The results indicate that the sensitivity of mussels to NaCl under the different test conditions and durations were relatively similar, although the younger juveniles could be more sensitive than the 2-mo-old juveniles, a starting age recommended by ASTM International (2017).…”
Section: Discussionmentioning
confidence: 99%
“…To compare the relative sensitivity of mussels with other freshwater species, toxicity databases were compiled by adding Freshwater mussel sensitivity to different chemicals Environ Toxicol Chem 36, 2017 789 the mussel toxicity data from the present study to additional databases, including the USEPA ICE database [19,20] for alachlor, metolachlor, chloride (as NaCl), potassium (as KCl), calcium chloride, 2,4-dichlorophenoxyacetic acid, 4-nonylpgenol, azoxystrobin, bifenthrin, malathion, molinate, chromium (VI), and nickel; the databases used to derive USEPA water quality criteria for arsenic (V) [34], ammonia [35], copper [36], and carbaryl [37]; the database used to update water quality criteria for aluminum (D. Eignor, USEPA, Washington, DC, unpublished data); a zinc database [38]; a sulfate database representing a hardness range of 80 mg/L to 120 mg/L [16]; and the toxicity data from the companion study with the 2 snails and 3 other invertebrates (Ivey et al [23] in this issue) and unpublished toxicity data from acute toxicity tests conducted at the Columbia Environmental Research Center that met ASTM International test acceptability criteria, such as >90% control survival. Toxicity data for nickel and zinc were normalized to a hardness of 50 mg/L as CaCO 3 using the equations in the USEPA water quality criteria for nickel or zinc [34], and copper data were normalized using a biotic ligand model [36].…”
Section: Discussionmentioning
confidence: 99%
“…Species sensitivity comparisons among mussels and other freshwater organisms. In the expanded database with more chemicals and mussel species, Raimondo et al [20] found that, in general, C. dubia was less sensitive than mussels. Compared with the 5 mussels tested in the present study, the 2 snails had greater EC50s for ammonia, potassium, sulfate, and chromium but had similar EC50s for the other 6 chemicals.…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation